THE RELIGIOUS NARRATIVE OF FORMING THE SECURITY SYSTEM IN THE MIDDLE EAST - D. A. Mirgorod (Современная наука и инновации)
The contemporary security system in the Middle East is of a transit nature and is characterized by a high degree of volatility. One of the main reasons for this is the presence of a significant number of interfaith problems caused by religious narratives that are used as an ideological base by various regional and extra-regional forces.